The impacts of organochlorine pesticides on adverse human health outcomes: A second-order synthesis of mean effects and heterogeneity - Kyle Morrison; Lorenzo Ricolfi; Yefeng Yang; Ayumi Mizuno; Pietro Pollo; Malgorzata Lagisz; Shinichi Nakagawa (Journal of Hazardous Materials, 2026)

The impacts of pesticide exposure on fish conspecific interactions: A systematic review and meta-analysis - Kyle Morrison; Gabriel Melhado; Aneesh P.H. Bose; Rhiannon Eastment; Malgorzata Lagisz; Jack L. Manera; Marcus Michelangeli; Shiho Ozeki; Bob B.M. Wong; Yefeng Yang; Shinichi Nakagawa (Environmental Pollution, 2025)

Location‐Scale Meta‐Analysis and Meta‐Regression as a Tool to Capture Large‐Scale Changes in Biological and Methodological Heterogeneity: A Spotlight on Heteroscedasticity - Shinichi Nakagawa; Ayumi Mizuno; Kyle Morrison; Lorenzo Ricolfi; Coralie Williams; Szymon M. Drobniak; Malgorzata Lagisz; Yefeng Yang (Global Change Biology, 2025)
Heterogeneity is a defining feature of ecological and evolutionary meta‐analyses. While conventional meta‐analysis and meta‐regression methods acknowledge heterogeneity in effect sizes, they typically assume this heterogeneity is constant across studies and levels of moderators (i.e., homoscedasticity). This assumption could mask potentially informative patterns in the data. Here, we introduce and develop a location‐scale meta‐analysis and meta‐regression framework that models both the mean (location) and variance (scale) of effect sizes. Such a framework explicitly accommodates heteroscedasticity (differences in variance), thereby revealing when and why heterogeneity itself changes. This capability, we argue, is crucial for understanding responses to global environmental change, where complex, context‐dependent processes may shape both the average magnitude and the variability of biological responses. For example, differences in study design, measurement protocols, environmental factors, or even evolutionary history can lead to systematic shifts in variance. By incorporating hierarchical (multilevel) structures and phylogenetic relationships, location‐scale models can disentangle the contributions from different levels to both location and scale parts. We further attempt to extend the concepts of relative heterogeneity and publication bias into the scale part of meta‐regression. With these methodological advances, we can identify patterns and processes that remain obscured under the constant variance assumption, thereby enhancing the biological interpretability and practical relevance of meta‐analytic results. Notably, almost all published ecological and evolutionary meta‐analytic data can be re‐analysed using our proposed analytic framework to gain new insights. Altogether, location‐scale meta‐analysis and meta‐regression provide a rich and holistic lens through which to view and interpret the intricate tapestry woven with ecological and evolutionary data. The proposed approach, thus, ultimately leads to more informed and context‐specific conclusions about environmental changes and their impacts.

Evidence of eastern rockhopper penguin feeding on a key commercial arrow squid species - Hugo R. Guímaro; David R. Thompson; Kyle W. Morrison; Joana Fragão; Ricardo S. Matias; José C. Xavier (Polar Biology, 2025)
Cephalopods are crucial to the Southern Ocean ecosystem, connecting top predators with mid-trophic organisms, yet their ecology in the Pacific sector is not well understood. This research used stable isotope analysis to explore the habitat and trophic ecology of cephalopods found in the diet of eastern rockhopper penguins ( Eudyptes chrysocome filholi ) around Campbell Island, a New Zealand sub-Antarctic island. Eastern rockhopper penguins were used as biologic samplers, revealing some differences in cephalopod diversity and ecology between two breeding seasons—1986–87 and 2012–13—, and the squid Nototodarus sloanii , a commercially valuable species, was described for the first time in the 2012–13 season. Stable isotope values ( δ 13 C and δ 15 N) for the squid species Moroteuthopsis ingens were consistent between seasons, indicating ecological stability, whereas the octopod species Octopus campbelli showed changes, suggesting shifts in habitat and feeding. Warmer oceanic temperatures in 2012–13 may have facilitated the emergence of N. sloanii on the diet of the eastern rockhopper penguins. These findings highlight potential changes in cephalopod biodiversity in the Pacific sector of the Southern Ocean, emphasizing the need for further research on ecological dynamics of this region.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

A systematic evidence map and bibliometric analysis of the behavioural impacts of pesticide exposure on zebrafish - Kyle Morrison; Yefeng Yang; Manuela Santana; Malgorzata Lagisz; Shinichi Nakagawa (Environmental Pollution, 2024)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Potential for redistribution of post‐moult habitat for Eudyptes penguins in the Southern Ocean under future climate conditions - Cara‐Paige Green; David B. Green; Norman Ratcliffe; David Thompson; Mary‐Anne Lea; Alastair M. M. Baylis; Alexander L. Bond; Charles‐André Bost; Sarah Crofts; Richard J. Cuthbert; Jacob González‐Solís; Kyle W. Morrison; et al. (Global Change Biology, 2023)
Anthropogenic climate change is resulting in spatial redistributions of many species. We assessed the potential effects of climate change on an abundant and widely distributed group of diving birds, Eudyptes penguins, which are the main avian consumers in the Southern Ocean in terms of biomass consumption. Despite their abundance, several of these species have undergone population declines over the past century, potentially due to changing oceanography and prey availability over the important winter months. We used light‐based geolocation tracking data for 485 individuals deployed between 2006 and 2020 across 10 of the major breeding locations for five taxa of Eudyptes penguins. We used boosted regression tree modelling to quantify post‐moult habitat preference for southern rockhopper ( E. chrysocome ), eastern rockhopper ( E. filholi ), northern rockhopper ( E. moseleyi ) and macaroni/royal ( E. chrysolophus and E. schlegeli ) penguins. We then modelled their redistribution under two climate change scenarios, representative concentration pathways RCP4.5 and RCP8.5 (for the end of the century, 2071–2100). As climate forcings differ regionally, we quantified redistribution in the Atlantic, Central Indian, East Indian, West Pacific and East Pacific regions. We found sea surface temperature and sea surface height to be the most important predictors of current habitat for these penguins; physical features that are changing rapidly in the Southern Ocean. Our results indicated that the less severe RCP4.5 would lead to less habitat loss than the more severe RCP8.5. The five taxa of penguin may experience a general poleward redistribution of their preferred habitat, but with contrasting effects in the (i) change in total area of preferred habitat under climate change (ii) according to geographic region and (iii) the species (macaroni/royal vs. rockhopper populations). Our results provide further understanding on the regional impacts and vulnerability of species to climate change.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Impacts of zebra mussels (Dreissena polymorpha) on isotopic niche size and niche overlap among fish species in a mesotrophic lake - Alexandra L. Morrison; Mary A. Thelen; Sarah E. Howe; Kyle D. Zimmer; Brian R. Herwig; David F. Staples; Margaret C. McEachran (Biological Invasions, 2021)

Predation by New Zealand sea lions and Brown Skuas is causing the continued decline of an Eastern Rockhopper Penguin colony on Campbell Island - Kyle W. Morrison; Doug P. Armstrong; Phil F. Battley; Sarah E. Jamieson; David R. Thompson (Polar Biology, 2017)

Spatial distribution and the value of green spaces for urban red-tailed hawks - Joan L. Morrison; Isabel G. W. Gottlieb; Kyle E. Pias (Urban Ecosystems, 2016)

The canalized parental roles of a Eudyptes penguin constrain provisioning and growth of chicks during nutritional stress - Kyle W. Morrison; Neil C. Morrison; Raymond M. Buchheit; Rob Dunn; Phil F. Battley; David R. Thompson (Behavioral Ecology and Sociobiology, 2016)

Population dynamics of Eastern Rockhopper Penguins on Campbell Island in relation to sea surface temperature 1942–2012: current warming hiatus pauses a long-term decline - Kyle W. Morrison; Phil F. Battley; Paul M. Sagar; David R. Thompson (Polar Biology, 2015)

Higher trophic level prey does not represent a higher quality diet in a threatened seabird: implications for relating population dynamics to diet shifts inferred from stable isotopes - Kyle W. Morrison; Sarah J. Bury; David R. Thompson (Marine Biology, 2014)

Transcription mapping and expression analysis of candidate genes in the vicinity of the mouse Loop-tail mutation - D. Alan Underhill; Kyle J. Vogan; Zoha Kibar; Jodi Morrison; Johanna Rommens; Philippe Gros (Mammalian Genome, 2000)